(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: This study is carried out with an objective to comparative investigation of antibacterial and antifungal potentials of four medicinal plants of Pakistan. The ethanol extract of Aloe vera (gel), Azadirachta indica (bark), Salvadora persica (stem) and Syzygium aromaticum (oil) were used against Streptococcus salivarius, Streptococcus pyogenes, Streptococcus mutans, Streptococcus uberis, Streptococcus pneumoniae and Candida albican. Method: Antimicrobial activity was evaluated by agar well diffusion assay at 20, 10 and 5mg/ml concentration of test samples. Ampicillin is used as standard drug. The sensitivity of microorganisms to all selected parts of four plants were compared with each other and with standard antibiotics. All plant extracts showed increase in antimicrobial activity with increase in concentration. Result: Among all extracts the extract of A. vera present maximum antimicrobial activity in dose dependent manner with highest zone of inhibition of 29.1±3.2 at 20mg/ml conc. while S. persica exhibited minimum antimicrobial activity with zone of inhibition 17.5±2.5 at 20mg/ml conc. Conclusion: The present study suggested that theses medicinal plants contain certain compounds which can be used to discover bioactive natural products to cure common dental problems, which are safe and economical. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.284-290